1995
DOI: 10.1093/jnci/87.8.573
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Carboplatin Clearance From Standard Morphological and Biological Patient Characteristics

Abstract: This formula for the determination of carboplatin clearance can permit individualized determination of carboplatin dosage in adults by simply multiplying the calculated carboplatin clearance by the area under the curve for the desired dosage administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(96 citation statements)
references
References 0 publications
1
95
0
Order By: Relevance
“…The dose of carboplatin was determined by multiplying the target AUC of 5 by the carboplatin CL, which was predicted with the Chatelut formula (Chatelut et al, 1995) using the Jaffé method to measure serum creatinine. The value of serum creatinine obtained using the enzymatic method (X) were converted to that using the Jaffé method (Y) with the formula Y ¼ 0.97X þ 0.27.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The dose of carboplatin was determined by multiplying the target AUC of 5 by the carboplatin CL, which was predicted with the Chatelut formula (Chatelut et al, 1995) using the Jaffé method to measure serum creatinine. The value of serum creatinine obtained using the enzymatic method (X) were converted to that using the Jaffé method (Y) with the formula Y ¼ 0.97X þ 0.27.…”
Section: Treatmentmentioning
confidence: 99%
“…Accordingly, we conducted a phase I trial with carboplatin and weekly doses of irinotecan, and found that 11 of 13 SCLC patients had an objective response, the response rate being 85% (complete response (CR), 31%; partial response (PR), 54%) (Fukuda et al, 1999). Pharmacodynamic studies have been performed to predict the clearance and administer the appropriate dose of carboplatin in individual patients (Egorin et al, 1985;Calvert et al, 1989;Chatelut et al, 1995;Duffull and Robinson, 1997;Mountain and Dresler, 1997). In a prior phase I study, we prospectively evaluated the Chatelut formula, and reported that the predicted carboplatin clearance (CL) was closely correlated with the actual CL, and the actual AUCs of carboplatin nearly reached the target AUC of 5 (Fukuda et al, 1999).…”
mentioning
confidence: 99%
“…Afterwards carboplatin was given as a 30 min intravenous infusion. The area under the concentration-time curve (AUC) used for carboplatin was 6 mg/ml min and the dose of carboplatin was calculated according to the Chatelut formula [23]. Both agents were administered every 3 weeks, on an outpatient basis.…”
Section: Treatment Schedule and Dose Modificationsmentioning
confidence: 99%
“…Patients with progressive disease or no response after the initial two cycles were taken off study. The carboplatin exposure in terms of area under the concentration-time curve (AUC) was estimated retrospectively using both the Calvert's (Calvert et al, 1989) and Chatelut's (Chatelut et al, 1995) formulae. Chest irradiation (45 Gy) was given for limited-disease (LD) patients after four cycles of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%